The Determination of Procalcitonin Concentration in Early-Onset Neonatal Infection: A Valuable Test Regardless of Prenatal Antibiotic Therapy. (April 2017) - Kordek, Agnieszka; Torbé, Andrzej; Tousty, Joanna; Łoniewska, Beata; Podraza, Wojciech; Nikodemski, Tomasz; Rudnicki, Jacek
The aim of this study was to assess the clinical usefulness of blood procalcitonin (PCT) levels for the diagnosis and therapeutic monitoring of early-onset neonatal sepsis (EONS). PCT as well as C-reactive protein (CRP) levels and white blood cell (WBC) count were measured in venous blood from 57 infected and 72 uninfected neonates. Differences between groups for PCT, CRP, and WBC levels were significant. The threshold value on the receiver operating characteristic curve in the prediction of EONS was 5.33 ng/mL for PCT, 9.3 mg/L for CRP, and 14.9 × 10 9 /L for WBC. There was no effect of antibiotic administered to the mother on PCT, CRP, and WBC levels in neonatal blood sampled before treatment of EONS. Evidently reduced PCT levels are observed after 2 days of treatment. The authors conclude that prenatal antibiotic therapy does not reduce the value of PCT levels in blood for the diagnosis of EONS.